2017
DOI: 10.19044/esj.2017.v13n16p233
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Financial Wellbeing of Public Sector Employees: A Critical Literature Review

Abstract: There is a great concern from researchers, government, and professional bodies about how consumers, households, students and employees manage their finances. A great number of people from both developed and developing countries are reported to be financially illiterate. Employees today are facing serious challenges in financial decision making that seems to emanate from the changes in financial markets and in social security pension schemes. They have access to financial literacy sessions at their workplaces y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 26 publications
2
45
0
3
Order By: Relevance
“…These results support the view of (Taft et al, 2013:Kamakia et al, 2017 which finds individuals who have a good financial literacy take financial wellbeing better and, individuals FWB that are consistently changed their logic and reasoning. Additionally, no statistically significant differences were found in the subgroups by demographic variables.…”
Section: Hypothesissupporting
confidence: 88%
“…These results support the view of (Taft et al, 2013:Kamakia et al, 2017 which finds individuals who have a good financial literacy take financial wellbeing better and, individuals FWB that are consistently changed their logic and reasoning. Additionally, no statistically significant differences were found in the subgroups by demographic variables.…”
Section: Hypothesissupporting
confidence: 88%
“…Several other studies that also linked financial literacy with financial wellbeing, such as the study of Sabri & Zakaria (2015) and Zulfiqar & Bilal (2016), which claimed that financial literacy positively affects financial wellbeing. However, Kamakia, Mwangi & Mwangi (2017) concluded that financial literacy does not affect financial wellbeing.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…A person's level of financial literacy determines their ability to manage their resources properly throughout life. A person being able to manage funds/cash owned by being able to feel prosperous concerning his finances and conversely a decrease in one's wellbeing can arise due to poor financial management behaviour (Gerrans et al, 2014;Kamakia, Mwangi, & Mwangi, 2017;Zulfiqar & Bilal, 2016). Someone who has good financial literacy is shown by the behaviour in managing finances properly, that person can be said to be prosperous in terms of his finances, and to be claimed prosperous, a person must have high financial literacy by exhibiting good management behaviour (Mudzingiri, Mwamba, & Keyser, 2018;Munoz-Murillo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Almost 70% of Malaysians are in need of financial literacy support. Financial knowledge, ability and attitude towards financial matters is known as financial literacy (Kamakia et al, 2017;Remund, 2010). It leads to sound decision making and enhance an individual's financial well-being.…”
Section: Research Background Problem Statementmentioning
confidence: 99%